Hubungan Antara Penggunaan Alat Pelindung Telinga (APT) Dengan Keluhan Akibat Kebisingan Pada Pekerja Di Bagian Produksi PT. X - Ayu Nabilla; Perry Boy Chandra Siahaan; Wintah` Wintah; Fikri Faidul Jihad; Zakiyuddin Zakiyuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Noise is one of the physical hazards in the workplace that may cause various health complaints, particularly among workers in the palm oil processing industry. The use of Hearing Protection Devices (HPDs) is one of the preventive measures to reduce the adverse effects of noise exposure; however, its effectiveness depends on workers' compliance in using the devices properly and consistently. This study aimed to determine the relationship between compliance with Hearing Protection Device (HPD) use and noise-related complaints among productionworkers at Company X. This analytical observational study employed a cross-sectional design. The study involved 53 production workers selected using the total sampling technique. Data were collected using a questionnaire on HPD compliance and a questionnaire on noise-related complaints. Data were analyzed using Fisher's Exact Test. The results showed that most respondents complied with HPD use, while themajority still experienced noise-related complaints. Fisher's Exact Test indicated a significant relationship between compliance with HPD useand noise-related complaints (p-value = 0.043). The findings suggest that the use of HPDs alone is insufficient to prevent noise-related complaints. Therefore, comprehensive noise control measures, including engineering controls, administrative controls, and consistent supervision of HPD use, are necessary to reduce the risk of noise-related complaints among workers.